2020
DOI: 10.1039/d0ob01190h
|View full text |Cite
|
Sign up to set email alerts
|

An amide hydrogen bond templated [1]rotaxane displaying a peptide motif – demonstrating an expedient route to synthetic mimics of lasso peptides

Abstract: The rapid synthesis and characterization of an amide hydrogen bond templated [1]rotaxane – demonstrating a potential pathway to synthetic analogues of lasso peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Evans and coworkers also employed the DOSY technique to differentiate between two species which are only distinguishable from each other by the existence or absence of a mechanical bond, [1]rotaxane 12 and macrocycle 13 [23] . The D values measured in DMSO‐ d 6 were 1.28×10 −10 m 2 s −1 for 12 (Figure 6a) and 1.10×10 −10 m 2 s −1 for 13 (Figure 6b), which are in fully good agreement with the DFT simulated structures of the monomeric intertwined and non‐intertwined forms.…”
Section: Diffusion Ordered Nmr Spectroscopymentioning
confidence: 99%
“…Evans and coworkers also employed the DOSY technique to differentiate between two species which are only distinguishable from each other by the existence or absence of a mechanical bond, [1]rotaxane 12 and macrocycle 13 [23] . The D values measured in DMSO‐ d 6 were 1.28×10 −10 m 2 s −1 for 12 (Figure 6a) and 1.10×10 −10 m 2 s −1 for 13 (Figure 6b), which are in fully good agreement with the DFT simulated structures of the monomeric intertwined and non‐intertwined forms.…”
Section: Diffusion Ordered Nmr Spectroscopymentioning
confidence: 99%
“…Evans reported in 2020 the synthesis of the peptide [1] rotaxane 51 bearing amide bonds at both macrocycle and thread using more classical peptide chemical coupling methods (Scheme 13b). [62] Pre-assembled [2]rotaxane 50 was subjected to simultaneous deprotections of (1) the N-terminal side of the glycylglycylglycine sequence that substitutes the macrocycle and ( 2) the tert-butyl ester belonging to the glycine residue at the extremity of the encircled axle. Noteworthy, preservation of the interlocked architecture in 50 was ensured by the 1,3,5 substitution of the two trifluoromethylbenzamide moieties.…”
Section: Chempluschemmentioning
confidence: 99%
“…[1][2][3][4] [1]Rotaxanes refer to a classical type of MIM that consists of a ring-shaped macrocyclic wheel sheathed on its own linear axle, with the wheel and axle parts being linked by covalent bonds. 5,6 So far, numerous reports have been made on the design and preparation of macrocycle-based [1]rotaxanes. [7][8][9][10] For instance, Yan et al reported a novel method to prepare B21C7-based [1]rotaxanes.…”
mentioning
confidence: 99%